Health Information Quality and Patient Safety Performance: A Study at Awet Muda Narmada Regional Hospital - Syamsuriansyah, Syamsuriansyah; Hizriansyah, Hizriansyah (Media Publikasi Cendekia Indonesia, 2025)
This study examined the relationship between health information quality management and patient safety performance, identifying significant factors influencing safety outcomes. A quantitative approach was used, with the Hospital Survey on Patient Safety Culture (HSPSC) translated, culturally tailored, and validated for the local setting. The intervention consisted of comprehensive training in information quality, workflow alignment, and the implementation of standardized documentation procedures over 6 weeks. The study was conducted at Awet Muda Narmada Regional General Hospital in West Lombok, West Nusa Tenggara, Indonesia, with a sample size of 92 healthcare professionals, including physicians, nurses, and health information managers. The results demonstrated a 46-point improvement (from 52 to 98 on a 100-point Likert-type scale) in the dimension of